2006
DOI: 10.5132/jbse.2006.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Mercury Concentration in Suspension Solids of the Upper Madeira River, Rondônia

Abstract: The main goal of this work was going to study the spatial distribution of mercury in suspension solid in the upper Madeira river, comprehended between its formation by Beni and Mamoré rivers until Porto Velho’s city, using geostatistical analysis techniques. The samplings were performed in November 22th to 29th, 2003, and soon after, the total mercury was determined by atomic absorption spectrophotometer coupled cold vapor generation. The results revealed average increase in Hg concentrations at the Upper Made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
1
2
0
1
Order By: Relevance
“…The results obtained for the herbivorous fighters surprised, therefore, it was expected higher concentrations of HgMe for the species P. unifilis and P. expansa, because they are chelonians that feed on algae and other vegetal proteins deposited in the sediment of the river, in the same way that a greater concentration of capybara was suspected, since this animal usually lives in regions bordering rivers and uses them as a hiding place and protection against natural predators, as well as for reproduction, thus, it has a greater contact with the sediment of rivers. This result was expected since other studies (Almeida et al, 2014;Vergotti et al, 2009;Gomes et al 2006;Lechler et al, 2000) showed that the bottom sediments are the abiotic accumulates mercury in the Amazonian rivers. It is suggested, therefore, the importance of conducting further research aimed at understanding the behavior of mercury in the wild animal organism.…”
Section: Fig 2 -Mean Concentrations Of Hgme In Fish Muscle Tissue By Dietary Habitsupporting
confidence: 65%
“…The results obtained for the herbivorous fighters surprised, therefore, it was expected higher concentrations of HgMe for the species P. unifilis and P. expansa, because they are chelonians that feed on algae and other vegetal proteins deposited in the sediment of the river, in the same way that a greater concentration of capybara was suspected, since this animal usually lives in regions bordering rivers and uses them as a hiding place and protection against natural predators, as well as for reproduction, thus, it has a greater contact with the sediment of rivers. This result was expected since other studies (Almeida et al, 2014;Vergotti et al, 2009;Gomes et al 2006;Lechler et al, 2000) showed that the bottom sediments are the abiotic accumulates mercury in the Amazonian rivers. It is suggested, therefore, the importance of conducting further research aimed at understanding the behavior of mercury in the wild animal organism.…”
Section: Fig 2 -Mean Concentrations Of Hgme In Fish Muscle Tissue By Dietary Habitsupporting
confidence: 65%
“…Como o lago Puruzinho possui grande carga de matéria orgânica em decomposição, principalmente nos período de cheia, podese classificá-lo com um lago de água preta (Sioli & Klinge, 1964), caracterizado por baixos valores de pH. A condutividade foi maior na coleta de outubro de 2004 (15,2 µS cm -1 ) e menor nas coletas de fevereiro de 2004 (8,3 µS cm -1 ) e maio de 2005 (9,2 µS cm -1 ) No período de seca, o lago Puruzinho passa a receber influência da água branca do rio Madeira, e este, rico em sólidos em suspensão (Gomes et al, 2006), tende a elevar os valores de condutividade do lago Puruzinho. Apesar de o presente estudo ter avaliado Hg total, é possível observar pelos parâmetros físicos e químicos da água que o lago Puruzinho apresenta características favoráveis à metilação do Hg (Lacerda & Solomons, 1992), como baixos valores de pH e oxigênio dissolvido e elevadas temperaturas.…”
Section: Resultsunclassified
“…In the waters of the Madeira River, the concentrations found of both Hg and MeHg are within the range reported in the Amazon region by several authors (Pfeiffer et al, 1991;Aula et al, 1995; Biota sediment accumulation factor: BSAF; THg: total Hg; MeHg: methylmercury; S: sediment; SS: suspended solids; Ppk: Phytoplankton; Zpk: Zooplankton; BM: benthic macroinvertebrates; a,b,c: different letter superscripts denote statistically significant differences by Bonferroni correction test; we accepted p < .05 as statistically significant. Malm et al, 1989;Kannan et al, 1998;Bastos et al, 2006). It seems that past anthropogenic sources of Hg associated with gold extraction and hydroelectric reservoirs (in the Madeira River) had less impact on the measured Hg variables than the natural environmental conditions associated with water pH (Table 1).…”
Section: Discussionmentioning
confidence: 98%
“…1). Its main course is mostly "white" water from the Andean piedmont, running through sedimentary and metamorphic rocks (Gomes et al, 2006;Queiroz et al, 2011). Clear waters are found in ancient formations such as areas of the Shields (Irion, 1984).…”
Section: Introductionmentioning
confidence: 99%